The Influence of Organizational Commitment on Employee Performance (Case Study at PT. Herlinah Cipta Pratama) - Syaifuddin; Egi Maulana Yusuf (PT Inovasi Pratama Internasional, 2023)
This research is motivated by employee performance that is not yet optimal, especially in terms of organizational commitment. Some employees have not fully fulfilled the responsibilities and tasks that have been given by the company so that it affects the decline in employee performance. The purpose of this study is to determine organizational commitment at PT. Herlinah Cipta Pratama, to determine the performance of employees at PT. Herlinah Cipta Pratama and to find out how organizational commitment influences employee performance at PT. Herlinah Cipta Pratama. The research method used is quantitative with a descriptive and causal associative approach with a total of 70 respondents. Data analysis techniques using instrument validity tests and instrument reliability tests, simple correlation tests, coefficient of determination tests and hypothesis testing (T test) using SPSS (Statistical Product and Service Solutions) version 25. The results of the study prove that organizational commitment has a positive effect on employee performance at PT. Herlinah Cipta Pratama.